Stability of pure even-aged conifer stands in Portugal - Nunes, Luís (2010)
The slenderness coefficient of a tree is defined as the ratio of total height (h) to diameter at 1.3 m above ground (d). For the stand level, the slenderness coefficient is calculated using the quadratic mean diameter and the height of the mean tree as (hg/dg). There is well known that a straight relationship exist between the slenderness coefficient of the stands and the risk of stem breakage or tree fall due to abiotic factors such as the wind or snow. When ignoring or neglecting the aspects related to the stands stability, risks of wood production losses caused by storms can be high. Storms of 1982 and 1999 with wind speeds above 100 Km h-1 have particularly damaged extensive forest areas (mainly conifer stands) in the Central European Plain. As the result of learning from these occurrences, the combined effect of hg/dg coefficient and dominant height was found to be a useful and practical criterion for the diagnosis of the stability situation (wind-firmness) of pure even-aged stands of conifer species. Three stability levels have been considered which could be presented in a simple diagram: optimum, moderate and instable. A stand that is let to grow naturally, without intervention, quickly attains the instability level, being more vulnerable to winds of great strength. In Portugal there have been no meaningful episodes of windthrow in conifer stands where the maritime pine (Pinus pinaster Ait.) is the most representative species. Future climate scenarios forecast an increase in the growth potential in some forest sites. Higher dominant heights may increase the risk of tree damage caused by violent storms. In this study, an evaluation of the stability status of Portuguese pure even-aged stands of maritime pine and other conifer species is made, based on data from the national forest inventory (NFI) and using stability diagrams. The analysis is undertaken by territorial units of level II (NUT II) with the support of GIS software. Characteristics of the stands that lay in each stability level are compared and discussed.